Methuselah's daughters: Paternal age has little effect on offspring number and quality in Cardiocondyla ants. Issue 23 (8th November 2018) - Heinze, Jürgen; Hanoeffner, Michaela; Delabie, Jacques H. C.; Schrempf, Alexandra
Abstract: Male age may directly or indirectly affect the fitness of their female mating partners and their joint progeny. While in some taxa of insects, old males make better mates and fathers, young males excel in others. Males of most social Hymenoptera are relatively short lived and because of testis degeneration have only a limited sperm supply. In contrast, the wingless fighter males of the ant Cardiocondyla obscurior live for several weeks and produce sperm throughout their lives. Wingless males engage in lethal combat with rival males and the winner of such fights can monopolize mating with all female sexuals that emerge in their nests over a prolonged timespan. Here, we investigate if male age has an influence on sperm quality, the queen's lifespan and productivity, and the size and weight of their offspring. Queens mated to one‐week or six‐week‐old males did not differ in life expectancy and offspring production, but the daughters of young males were slightly heavier than those of old males. Our data suggest negligible reproductive senescence of C. obscurior males even at an age, which only few of them reach. This matches the reproductive strategy of Cardiocondyla ants, in which freshly emerging female sexuals rarely have the option to mate with males other than the one present in their natal nest. Abstract : The age of a male mating partner typically has a strong effect on the fitness of the female and its offspring. Males of the ant Cardiocondyla obscurior are characterized by an extraordinary lifelong spermatogenesis. Here we show that old age of C. obscurior males neither effects fecundity and longevity of the queen nor the size of the offspring, suggesting negligible reproductive senescence.